The Coming of the Pythia - Latte, Kurt (Harvard theological review, 1940)
The commonly accepted idea of the evolution of the Delphian mantic may be outlined thus: There was first an oracle of the Mother Earth, working by incubation (cf. p. 16, later). Later on, Apollo took possession of it, but its character remained unchanged: the believers continued to receive revelation in dreams. Afterwards Dionysos went to Delphi and with him ecstasy entered into the cult. It was not until then that oracles were given by an inspired, i.e. ecstatic, priestess called Pythia.